The Influence of Digital Payment, Use of Accounting Information and Financial Literacy on MSME Income in Bukittinggi City - Fadhilah, Zahra Nur; Putra, M. Shama; Putri, Anne (ADPEBI, 2024)
This research aims to determine the influence of Digital Payment, Use of Accounting Information and Financial Literacy on MSME Income in Bukittinggi City. The type of data in this research is primary data by distributing questionnaires to MSMEs in Bukittinggi City. The sampling technique used purposive sampling, the number of MSME actors sampled was 90 people. The analysis technique uses tests with the help of SmartPLS software version 4. Based on the hypothesis testing that has been described based on the research results, it shows that: (1) Digital Payment has a positive and significant effect on MSME income, (2) The use of Accounting Information has a positive and significant effect on MSME income, (3) Financial Literacy has a positive and significant effect on MSME income.